Unusual oxidation behavior of light metal hydride by tetrahydrofuran solvent molecules confined in ordered mesoporous carbon. Issue 1 (20th August 2013) - Klose, Markus; Lindemann, Inge; Minella, Christian Bonatto; Pinkert, Katja; Zier, Martin; Giebeler, Lars; Nolis, Pau; Baró, Maria Dolors; Oswald, Steffen; Gutfleisch, Oliver; Ehrenberg, Helmut; Eckert, Jürgen
Abstract